Comparison of Optimal and Intelligent Sway Control for a Lab-Scale Rotary Crane System - Mohd Ashraf, Ahmad; Mohd Anwar, Zawawi (2010)
This paper presents investigations of sway feedback control approaches for a rotary crane system with disturbance effect in the dynamic system. Linear Quadratic Regulator (LQR) controller and Proportional-Derivative (PD)-type Fuzzy Logic controller are the techniques used in this investigation to actively control the sway of rotary crane system. A lab-scale rotary crane system is considered and the dynamic model of the system is derived using the Euler-Lagrange formulation. A complete analysis of simulation results for each technique is presented in time domain and frequency domain respectively. Performances of the controller are examined in terms of sway suppression and disturbances cancellation. Finally, a comparative assessment of the impact of each controller on the system performance is presented and discussed.